SCLERODERMA: A CASE REPORT* - Gülay Altan; Taha Emre Köse; Tamer Lütfi Erdem; İlknur Özcan (Istanbul University, 2015)
Scleroderma is an autoimmune connective tissue disorder which is characterized by fibrosis of visceral organs, skin and blood vessels. This condition can be localized or systemic. Its estimated prevalence is 250 cases in a million and it is more common in women than in men. Resorption of the mandibular angle and coronoid process can be observed in patients with scleroderma. Pressure of fibrous mucocutaneous tissues is thought to be the cause of the resorption. Decreased number of wrinkles due to sclerosis and distinct facial features because of the atrophy of ala nasi are among common clinical characteristics of this condition. The aim of this case report is to present a 40-year-old female patient with scleroderma who presented with signs of resorption at the angle of mandible, coronoid process, as well as widening of the periodontal space.